Exploring the spiritual foundations of public health leadership - Koh, Howard K.; Tso, Cathy C.; Dougherty, Cyra Perry; Lazowy, Emily E.; Heberlein, Chelsea P.; Phelps, Fawn A. (Frontiers in Public Health, 2023)
The Covid-19 pandemic has laid bare the challenges of public health leadership. Faced with criticism, threats, and even violence, many public health leaders have left the field. A healthier future for the nation may well rest on training aspiring public health leaders to build deeper capacity for perseverance, healing, and resilience. Reflecting the growing experience of a team of public health educators at the Harvard T.H. Chan School of Public Health (Harvard Chan), this article offers recommendations for public health schools to recognize, and incorporate into leadership education, themes of spirituality—ie, the way people seek ultimate meaning and purpose and deep connectedness to something larger than themselves. Doing so can serve as a foundation for the lifelong journey of leadership. Over the past decade, Harvard Chan has incorporated meaning, purpose, and connectedness themes to complement more traditional coursework addressing research and translation. While many established leadership frameworks address the “what” and “how” of career development, the spirituality framework can support aspiring leaders to more fully understand their “why” and its alignment with challenging work. Such a deeply personal topic, traditionally kept private, has been shared and nurtured in Harvard Chan classrooms through a range of pedagogical strategies including personal reflection, one-on- one coaching, experiential learning, case discussions, and candid conversations with public health leaders. By encouraging a values-based foundation for decision-making in crises and difficult leadership moments, such grounding can help aspiring leaders navigate the challenges of public health leadership that inevitably lie ahead.